Effect of vaginal gel containing propolis extract and oral metronidazole pill on dyspareunia in woman with trichomoniasis at Isfahan in 2019 - Seyede Shadi Taghavian; Afsaneh Yekdaneh; Hatav Ghasemi Tehrani; Mahboubeh Valiani; Siamak Alian; Reza Beiranvand (Mashhad University of Medical Sciences, 2021)
Introduction:Trichomoniasis is the most common non-viral sexually transmitted infection which is associated with several complications. Propolis is a bee product and contains tanen, flavonoids and volatile oils, so it has antiprasitic activity. This study was performed with aim to compare the effect of propolis gel and metronidazole tablet on dyspareunia. Methods:This clinical trial study was conducted in 2019 on 102 non-pregnant married women with complains of Trichomoniasis clinical symptoms referred to the gynecology clinics in Isfahan. They were divided into two groups of experiment (propolis gel) and control (metronidazole tablet). Participants were treated for 7 days. Dyspareunia was assessed using the visual pain scale (VAS) with a range of 0-10. Data were analyzed by SPSS software (version 20) and independent T-test, fisher exact test, ANCOVA and Chi-square tests. P<0.05 was considered statistically significant. Results: During all steps of the study, no significant differences were observed between the two groups in type and mean severity of pain. However, after adjustment of dyspareunia pre-intervention and 2 weeks after the intervention, the score of dyspareunia in the experiment group was 0.882 lower than the control group; this difference was statistically significant (P=0.009). In the experiment group, all of participants with post coital bleeding/spotting were completely treated, while no improvement was observed in the control group. Conclusion: Vaginal gel containing propolis extract has positive therapeutic effect on dyspareunia. It has least effect on the vaginal epithelium, without GI and neurologic side effects.